2014
DOI: 10.1590/s1517-83822014005000034
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant coagulase-negative staphylococci from healthy dogs in Nsukka, Nigeria

Abstract: The occurrence, resistance phenotype and molecular mechanisms of resistance of methicillin-resistant staphylococci from groin swabs of 109 clinically healthy dogs in Nsukka, Nigeria were investigated. The groin swab samples were cultured on mannitol salt agar supplemented with 10 μg of cloxacillin. Sixteen methicillin-resistant coagulase negative staphylococci (MRCoNS), all harbouring the mecA gene were isolated from 14 (12.8%) of the 109 dogs studied. The MRCoNS isolated were: S. sciuri subspecies rodentium, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 27 publications
1
46
4
Order By: Relevance
“…As problems with breakpoints for NAS have been noted before (Nemeghaire et al, 2014b(Nemeghaire et al, , 2014c, it may be necessary to evaluate the breakpoints at staphylococcal species level. Most genes have already been described among NAS of animal origin (Bhargava and Zhang, 2012;Chah et al, 2014;Frey et al, 2013;Kern and Perreten, 2013;Nemeghaire et al, 2014bNemeghaire et al, , 2014cWeiß et al, 2014;Wendlandt et al, 2013). The presence of other genes or combination of genes was particularly relevant in certain species.…”
Section: Article In Pressmentioning
confidence: 98%
“…As problems with breakpoints for NAS have been noted before (Nemeghaire et al, 2014b(Nemeghaire et al, , 2014c, it may be necessary to evaluate the breakpoints at staphylococcal species level. Most genes have already been described among NAS of animal origin (Bhargava and Zhang, 2012;Chah et al, 2014;Frey et al, 2013;Kern and Perreten, 2013;Nemeghaire et al, 2014bNemeghaire et al, , 2014cWeiß et al, 2014;Wendlandt et al, 2013). The presence of other genes or combination of genes was particularly relevant in certain species.…”
Section: Article In Pressmentioning
confidence: 98%
“…The mechanisms responsible for antimicrobial resistance in CNS are identical to those occurring in S. aureus (Livermore, 2000). Reports of methicillin-resistant strains among CNS are challenging due to the large proportion of methicillin-resistant strains and increasing numbers of isolates reinforcing the need to revise their importance to food safety (Bhargava and Zhang, 2014; Chah et al, 2014; Osman et al, 2016a,b). Therefore, screening of these elements is important for public health and despite the importance of such a screen, limited data are available for CNS at the species level among the chicken retail meat.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to the study by Elena G et al who reported a high rate of methicillin resistance, 81.3% with all MRCoNS isolates that were methicillin resistant also resistant to tetracycline However in the present study we found lower degree of association between MRCoNS and tetracycline with 25% of CoNS were co-resistant to tetracycline, showed that 74% of clinically healthy dogs harbored CoNS in their nares, from which 23.7%, 16.9%, 5.1% were resistant to penicillin, erythromycin and tetracycline respectively. 39 Huber et al from Switzerland showed S.sciuri as most prevalent species among all the CoNS isolates from which nasal MRCoNS rate was observed as 67% and 60.2% among pig farmers and J. Commun. Dis.…”
Section: Discussionmentioning
confidence: 99%